Trends in the functional development of the Public Prosecutor’s Office in Ukraine outside the criminal justice system: in search of doctrinal guidelines - Stefanchuk, M. M.; Legkykh, K. V. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
This study attempts to find doctrinal guidelines and identify trends in the functional development of the Public Prosecutor’s Office outside the criminal justice system. It is established that legal doctrine, as a coherent system of conceptual views contained, in particular, in policy documents of a political nature which identify problematic aspects and determine the strategic prospects for the legal development of the State, forms the conceptual basis for rulemaking. It is stated that one of the important conceptual documents in the field of reforming the justice system in Ukraine is the Strategy for the Development of this system, which, among other things, contains issues that determine the trends in the development of not only the Judiciary, but also the Prosecution and the Bar as related legal institutions that facilitate the delivery of justice by the courts. It is argued that the change in the conceptual approach to understanding the functions of the Public Prosecutor’s Office in Ukraine at the present stage of state-building is becoming explicit, in particular, through the prism of interpretative opinions of the Constitutional Court of Ukraine as a projection of constitutional doctrine, which is of particular importance for the formation of current trends in the legal status of the Public Prosecutor’s Office in the system of public authorities in general, as well as its functional direction, in particular, outside the criminal justice sphere. It is proved that the following trends in the functional development of the Public Prosecutor’s Office in Ukraine outside the criminal justice system are formed: leaving out of the reform attention the needs for improving legislative regulation and enhancing the effectiveness of the Public Prosecutor’s Office powers outside the criminal justice system; deviation from the principle of subsidiarity of prosecutorial representation as one of the principles which should be followed by the public prosecution services if they are vested with powers outside the criminal justice system; elimination of shortcomings in the legislative regulation of the representative function of the Public Prosecutor’s Office by using the possibilities of the institution of constitutional complaint. Promising areas for further scientific research in the area of the issues under study are identified with a view to developing a comprehensive and systematic conceptual approach to the doctrinal substantiation of functional trends in the development of the Public Prosecutor’s Office in Ukraine in strategic program documents, and to forming a uniform and well-established approach to understanding the legal nature of the Public Prosecutor’s Office’s activities outside the criminal justice system.